Small and Medium Size Enterprises, Credit Supply Shocks, and Economic Recovery in Europe - Klein, Nir. (Washington, D.C. : International Monetary Fund, 2014)
The limited access to bank credit in recent years has increased the pressure on small and medium size enterprises (SMEs), forcing them to scale down investment plans and production. This paper, which explores the macroeconomic implications of this channel, finds evidence that countries with high prevalence of SMEs tended to recover more slowly from the global financial crisis than their peers, implying that the interaction of the economic structure and access to bank financing plays a critical role in episodes of economic recovery. This conclusion is reinforced by a VAR estimation, which demonstrates that a negative credit supply shock applied to SMEs has an adverse effect on economic activity, and this impact is amplified in countries that have a high share of SMEs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet